Sheep manure organic fertilizer is an effective strategy to promote strawberry growth by improving soil physicochemical properties and microbiota - Zha, Yan; Liu, Aichun; Lai, Wenguo; Wang, Jianrong; Li, Xiaoyuan; Yu, Hong; Xiao, Wenfei (Frontiers in Environmental Science, 2024)
The use of organic fertilizers instead of chemical fertilizers can improve soil pH, help to maintain soil health and enable landowners to achieve organic or ecological-status agriculture. Rapeseed cake, sheep manure, and biofungal fertilizer are considered to be effective amendments to improve soil quality. However, there have been few studies on the effects of the three fertilizers on strawberry production, soil physicochemical properties, and inter-root soil microbial community structure. In this study, field experiments were conducted to investigate the differences in strawberry growth, quality, yield, and the structure and diversity of strawberry soil bacterial and fungal communities under four treatments: no organic fertilizer (CK), rapeseed cake organic fertilizer (T1), sheep manure organic fertilizer (T2) and bio-organic fertilizer (algae-optimized bacteria) (T3), the relationship between soil physicochemical properties and soil microbial diversity were analyzed. Our results have shown that these three amendments promoted the growth of strawberry to some extent. The effects of available phosphorus, ammonium nitrogen, sucrase, protease and urease under T2 treatment were significantly increased by 50.62%, 54.14%, 276.50%, 129.47%, 232.61% and 232.00%, respectively, compared with the control. The soil bacterial and fungi community were the most abundant and diversified under the T2 treatment. Soil physicochemical properties and soil key enzyme activities varied significantly under different fertilizer treatments, with the soil nutrient content and soil carbon and nitrogen metabolizing enzyme activities being highest under T2 treatment. A Pearson correlation analysis showed that soil organic matter was closely related to the diversity of soil microbial Running Title 2 communities. A redundancy analysis (RDA) showed that the main variables of the bacterial community included nitrate nitrogen (NN) and rapidly available potassium (RAP), while the main variables of the fungal community included alkaline dissolved nitrogen (ADN) and ammonium nitrogen (AN). Overall, different fertilizers promoted the release and transformation of soil nutrients by affecting the structure and diversity of bacterial and fungal communities in strawberry soils, which was beneficial to the supply of soil nutrients and the improvement of soil quality. The application of sheep manure organic fertilizer had the best soil improvement effect.